Application of 6,7-Indole Aryne Cycloaddition and Pd(0)-Catalyzed Suzuki-Miyaura and Buchwald-Hartwig Cross-Coupling Reactions for the Preparation of Annulated Indole Libraries - Thornton, Paul D. (2011)
The construction of an unprecedented class of an indole-based library, namely, a 6,7-annulated-4-substituted 93-member indole library, using a strategic combination of 6,7-indolyne cycloaddition and cross-coupling reactions under both Suzuki-Miyaura and Buchwald-Hartwig conditions is described. This work represents the first example of library development that employs the indole aryne methodology. Annulated indoles, with the exception of only a few biologically active natural products (i.e., the trikentrins, herbindoles, teleocidins, and nodulisporic acids), have no representation in the PubChem or MLSMR databases. These structural entities are therefore predicted to have unique chemical property space characteristics and a high probability of exhibiting interesting biological activity.